VALIDASI ALGORITMA ESTIMASI KONSENTRASI CHL-A DENGAN MENGGUNAKAN CITRA SATELIT LANDSAT 8(Studi Kasus : Laut Selatan Pulau Lombok, NTB) - Jaelani, Lalu Muhamad; Sulistyah, Umroh Dian; Winarso, Gathot (GEOID, 2016)
Lombok southern sea has a high marine productivity which signifies fertility of a body water. Chl-a is one of the factors associated with fertility in the Lombok southern sea. Remote sensing can be used for mapping the distribution of Chl-a more efficient and accurate to extract the physical parameters of the water. Physical parameters accuracy is derived from remote sensing data depending on atmospheric correction algorithms and algorithms model to calculate the concentration of Chl-a.In this study, Landsat 8 was used to validate the existing estimation concentration algorithm of Chl-a by in-situ data collected in Lombok southern sea. Atmospheric corrected reflectance by 6SV and Flaash, as well as surface reflectance product from USGS were used as input of that algorithm. The algorithm with 6SV-reflectance produced highest accuracy with NMAE of 26.095%.Instead of using existing algorithm, a new algorithm following local characteristics of Lombok southern sea was developed. The developed algorithm based on log Rrs( 4) and log (Rrs ( 5)) produced high  correlation (R2 = 0.551). Chl-a concentration estimation from Landsat 8 data, through atmospheric correction of 6SV produced NMAEof 13.484%.